Self organizing nets for pattern recognition (unsupervised learning based on discovery of cluster structure) / Kamaruzzaman Mohd. Sharif and Khairul Nazmi Mohd. Nor - Mohd. Sharif, Kamaruzzaman (1992)
The purpose of this project is to develope an organizing discipline by which neural network system can be designed for specific computations. Furthermore, it is also to recognize and make use of both the similarities and differences between well-established procedures and the newly proposed neural network approaches.